2019
DOI: 10.1038/s41598-018-36605-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiles of tumor-associated neutrophils reveal prominent roles in enhancing angiogenesis in liver tumorigenesis in zebrafish

Abstract: We have previously demonstrated the pro-tumoral role of neutrophils using a kras-induced zebrafish hepatocarcinogenesis model. To further illustrate the molecular basis of the pro-tumoral role, Tumor-associated neutrophils (TANs) were isolated by fluorescence-activated cell sorting (FACS) and transcriptomic analyses were carried out by RNA-Seq. Differentially expressed gene profiles of TANs from larvae, male and female livers indicate great variations during liver tumorigenesis, but the common responsive canon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…In view of several species-specific differences that might have a profound impact on the phenotypic and functional plasticity of neutrophils, human and mouse studies are separately discussed, highlighting similarities and differences between current findings in the two species. There is emerging evidence of heterogeneous populations of neutrophils in other organisms, such as the rhesus macaque [10], zebrafish [11,12], and horse [13], but these are beyond the scope of our discussion.…”
Section: Diversity and Heterogeneity Of Neutrophils: State Of The Artmentioning
confidence: 95%
“…In view of several species-specific differences that might have a profound impact on the phenotypic and functional plasticity of neutrophils, human and mouse studies are separately discussed, highlighting similarities and differences between current findings in the two species. There is emerging evidence of heterogeneous populations of neutrophils in other organisms, such as the rhesus macaque [10], zebrafish [11,12], and horse [13], but these are beyond the scope of our discussion.…”
Section: Diversity and Heterogeneity Of Neutrophils: State Of The Artmentioning
confidence: 95%
“…Further anti-tumour roles of neutrophils may include triggering apoptosis via activation of TRAIL [102] and promoting the activity of anti-tumour cytotoxic T lymphocytes [103]. In zebrafish, tumours also exhibit high levels of infiltrating neutrophils, which promote metastasis and express genes involved in angiogenesis and immunosuppression [104][105][106][107]. Anti-tumour neutrophil responses are yet to be described within zebrafish cancer models.…”
Section: Tumour-associated Neutrophilsmentioning
confidence: 99%
“…In addition, Bv8 is an important mediator of neutrophil-dependent angiogenesis, and blocking Bv8 function can inhibit angiogenesis and tumor growth (60,61). Recently, transcriptomic analyses demonstrated that pro-angiogenic genes including vegfa, itgb1, il1b, mmp14, and mmp9 as well as genes encoding other cell adhesion molecules, such as ilgals1 and igals3bp, are upregulated in TANs (62), further confirming a prominent role of neutrophils in promoting tumor angiogenesis.…”
Section: Early Metastatic Step-neutrophils At Tmementioning
confidence: 90%